Differential Responses to Price and Exchange Rate Influences in the Foreign Trade of Selected Industrial Countries - Wilson, John F.; Takacs, Wendy E. (The Review of Economics and Statistics, 1979)
John F. Wilson, Wendy E. Takacs, Differential Responses to Price and Exchange Rate Influences in the Foreign Trade of Selected Industrial Countries, The Review of Economics and Statistics, Vol. 61, No. 2 (May, 1979), pp. 267-279